Gastro-splenic fistula due to isolated splenic tuberculosis: an unusual case report - Baskar, Ashok K.; Ambedkar, M. J. Chandrabose; Lakshmanan, Anand; Satyanesan, Jeswanth (International Surgery Journal, 2025)
Gastrosplenic fistula is an uncommon condition, usually associated with splenic malignancies especially lymphomas. Few cases of gastrosplenic fistula are reported secondary to post traumatic splenic abscess, gastric ulcer, miliary tuberculosis. Isolated splenic tuberculosis is very rare. Gastrosplenic fistula due to isolated splenic tuberculosis is an extremely rare presentation. Here, we report a case of a 53-year-old man who presented with upper abdominal pain and fever. Computed tomography (CT) of abdomen showed multiple splenic abscess with splenic vein thrombosis. Upper gastrointestinal (GI) scopy showed fundal varies and submucosal nodular lesion at fundus. Endoscopic ultrasound showed splenic abscess probably infiltrating the fundus of stomach. He underwent open splenectomy with fistulous tract resection and pancreatic tail resection. Intraoperatively, the fistulous tract was identified at posterior aspect of fundus. The fistulous tract was excised and stomach edges were closed primarily. He recovered well without any complications. Histopathological examination showed splenic tuberculosis, and he was started on anti-tuberculosis treatment.